Assessment of hospital service quality parameters from patient, doctor and employees' perspectives. (2nd October 2020) - Singh, Ajwinder; Prasher, Ajay; Kaur, Navdeep
Abstract : The Indian healthcare industry has been growing at a tremendous pace and contributing a great deal towards the employment and revenue generation for the country. Recently, medical tourism has also gained a huge impetus as people from all over the globe visiting India for availing affordable and worldclass healthcare services. Hence, delivering effective healthcare service quality and understanding the perceptions of all stakeholders – i.e. patients, doctors and employees – has become very critical for the success of any healthcare centre. Over a period of time, service providers have been defining service quality parameters based on their own judgment and trying to deliver services as per their assumptions. However, patient satisfaction requires a proper synchronisation between what the patient expects and what the management perceives. For addressing this issue, six new dimensions were identified using SERVQUAL and termed it as 'HealQual' tool keeping in mind the needs of current Scenario. The paper would identify those healthcare service quality parameters which improve patient satisfaction and also generate priority weights from the perspectives of both service reviewer, i.e. patients and the service provider, i.e. doctors and employees.